Assessment of Knowledge, Attitudes, Practices, and Barriers Toward AI in Dental Prosthesis Design in Benghazi, Libya - Salma Elnaili (AlQalam Journal of Medical and Applied Sciences, 2026)
Artificial intelligence (AI) is increasingly influencing dental practice, particularly in prosthodontics, by enhancing precision, efficiency, and patient-specific outcomes. This study aimed to evaluate the knowledge, attitudes, practices, and perceived barriers related to AI-assisted prosthesis design among dentists and dental technicians in Benghazi, Libya. A cross-sectional online survey was conducted with 204 participants, including 189 dentists and 15 dental technicians, using a structured questionnaire covering knowledge, attitudes, practices, and perceived barriers, with responses recorded on a five-point Likert scale. Data analysis explored differences based on professional experience and role. Results showed moderate knowledge (mean ± SD: 3.48 ± 0.61) and generally positive attitudes (3.90 ± 0.71), but current practical use remained limited (practices 3.69 ± 0.65). The main barriers were lack of training (3.82 ± 0.90) and high cost (3.66 ± 0.90), while concern about AI replacing human roles was low (2.81 ± 1.14). Participants with more than 10 years of experience had significantly more favorable attitudes (p = 0.016) and perceived fewer barriers (p = 0.036). These findings indicate that dental professionals are receptive to AI in prosthesis design, but structured training, practical workshops, and improved accessibility of AI tools are essential to promote effective integration into clinical and laboratory workflows.